The Concept of Melayu Islam Beraja (MIB) as a Political Ideology and System of Governance in Brunei Darussalam - Ezra Kalyla; Nathania Aulia Damayanti; Elly Nurlia (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to understand how Melayu Islam Beraja (MIB) functions as a political ideology within the context of Brunei Darussalam’s absolute monarchy, to analyze its formation and the core components of Malay identity, Islam, and monarchy, as well as to evaluate its implementation in public policy, the education system, and governance. Furthermore, this research seeks to explore how MIB sustains monarchical legitimacy and political stability amid global modernization, while also identifying its implications for transparency, public participation, and modern governance in Brunei Darussalam. This study employs a qualitative descriptive approach using a literature study method. Primary data were obtained from official government documents of Brunei Darussalam, while secondary data were derived from academic literature. The research instrument used was a literature data recording sheet designed to organize findings from the literature review. The analytical technique applied was content analysis, which systematically interprets the content of texts and documents. The findings reveal that the concept of Melayu Islam Beraja (MIB) represents a political ideology that integrates Islamic, Malay, and monarchical values to affirm Brunei Darussalam’s national identity. This ideology serves both as a symbol of nationhood and as a foundation of political and moral legitimacy that underpins the Sultan’s authority within the absolute monarchy. MIB internalizes cultural and religious values to foster social cohesion and political stability amid global uncertainty. The governance system of Brunei demonstrates that political stability can be achieved through ideological and moral legitimacy rather than through electoral processes as in democratic systems. This model places trust, obedience, and moral responsibility as the fundamental pillars of state governance, where monarchical power is perceived as a manifestation of the nation’s religious and cultural values.